2017
DOI: 10.1080/16549716.2017.1291879
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of attending antenatal care at least four times in rural Ghana: analysis of a cross-sectional survey

Abstract: Background: Improving maternal health is a global challenge. In Ghana, maternal morbidity and mortality rates remain high, particularly in rural areas. Antenatal care (ANC) attendance is known to improve maternal health. However, few studies have updated current knowledge regarding determinants of ANC attendance. Objective: This study examined factors associated with ANC attendance in predominantly rural Ghana. Methods: We conducted a cross-sectional study at three sites (i.e. Navrongo, Kintampo, and Dodowa) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
55
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 37 publications
(43 reference statements)
21
55
5
Order By: Relevance
“…Economic status and maternal education were highly associated with utilisation of ANC, which corroborates with previous literature [19,20,21]. Younger maternal age at conception is also common among these women.…”
Section: Determinants Of Full Ancsupporting
confidence: 90%
“…Economic status and maternal education were highly associated with utilisation of ANC, which corroborates with previous literature [19,20,21]. Younger maternal age at conception is also common among these women.…”
Section: Determinants Of Full Ancsupporting
confidence: 90%
“…Six studies reported on the influence of husband/partner’s education on ANC use. Women whose husbands/partners had some education were more likely to access ANC services than those with less educated husbands/partners22 30 41 63 73 74 (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In 14 studies, women of high socioeconomic status (SES) attended at least four ANC visits more than those in the lower socioeconomic/wealth strata15 25 27 29 30 32 41 54 64 69 77 89–91 (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations